KONSEP, TEORI, DAN PRAKTIK OBLIGASI SYARIAH - Fauzulhaq, Muhammad Fadlilah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
One of the growing sharia finance instruments is sharia bond, sharia bonds are securities or certificate that contains the contract between funders (investors) with a given fund (the issuer), sharia bond is supported by the Sharia Securities Act (SBSN) on 9 April 2008, so it can grow a new optimism for national Islamic banking and finance industry. SBSN Act paved the way for the issuance of shria goverment and private bonds, in practice of Islamic bondsmay use multiple inclusion models in the form of mudhârabah, ijârah, and musyârakah.DOI: 10.15408/aiq.v5i2.2571